Investment philosophies : successful strategies and the investors who made them work - Damodaran, Aswath (Wiley, 2012)
"The guide for investors who want a better understanding of investment strategies that have stood the test of timeThis thoroughly revised and updated edition of Investment Philosophies covers different investment philosophies and reveal the beliefs that underlie each one, the evidence on whether the strategies that arise from the philosophy actually produce results, and what an investor needs to bring to the table to make the philosophy work. The book covers a wealth of strategies including indexing, passive and activist value investing, growth investing, chart/technical analysis, market timing, arbitrage, and many more investment philosophies. Presents the tools needed to understand portfolio management and the variety of strategies available to achieve investment success Explores the process of creating and managing a portfolio Shows readers how to profit like successful value growth index investors Aswath Damodaran is a well-known academic and practitioner in finance who is an expert on different approaches to valuation and investment This vital resource examines various investing philosophies and provides you with helpful online resources and tools to fully investigate each investment philosophy and assess whether it is a philosophy that is appropriate for you"--